The Effect of Price, Product Quality, and Service Quality on Consumer Satisfaction from an Islamic Perspective during the Covid-19 Pandemic - Kusuma, Nurul Rahmah; Rokhlinasari, Sri; Elkoshly, Salim (JURNAL INDO-ISLAMIKA, 2023)
The fierce competition in the era of globalization forces companies to improve innovation, creativity, quality and to ensure public safety in food consumption, especially due to the Covid-19 pandemic, when public trust in the food industry is weakened and the impact on the satisfaction of the consumers. It is influenced by several factors such as product quality, service quality, satisfactory amenities, price The purpose of this study is to analyze the effect of price, product quality, and service quality on customer satisfaction in KFC Cirebon restaurant. The research method uses a descriptive quantitative approach derived from the primary and secondary data. Primary data collection method uses a questionnaire survey and purposive sampling technique to determine the sample. This study used multiple linear regression analysis for data analysis, which was processed using SPSS 2.2 data processing application. The results of the survey with a total of 145 respondents showed that the variables of price, product quality, and service quality had a positive and significant effect on customer satisfaction of KFC Cirebon restaurant. Keywords: price, product quality, service quality, customer satisfaction, Covid-19.